2010
DOI: 10.3329/bmrcb.v35i3.3658
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical, phytochemical and toxicological studies of Ghagra shak (Xanthium strumarium L.) growing in Bangladesh

Abstract: The present study describes the ethnobotanical, phytochemical, and toxicological evaluations of Xanthium strumarium L. growing in Bangladesh. In toxicity evaluation on rats, the methanol extract of seedlings showed mortality, while both seedling and mature plant extracts raised the serum alanine transaminase and aspartate transaminase values and produced significant abnormalities in the histopathology of liver and kidney of rats. On the other hand, the aqueous soluble fraction of methanol extract of mature pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…In addition, several North American Indian tribes and Zuni tribes apply this plant to relieve constipation, diarrhoea and vomiting [1]. Besides, X. strumarium is also reported as a folk herbal medicine in Bangladesh for the treatment of urinary disorder, ear infection, diabetic, and gastric disorder [8].…”
Section: Traditional Usagesmentioning
confidence: 99%
“…In addition, several North American Indian tribes and Zuni tribes apply this plant to relieve constipation, diarrhoea and vomiting [1]. Besides, X. strumarium is also reported as a folk herbal medicine in Bangladesh for the treatment of urinary disorder, ear infection, diabetic, and gastric disorder [8].…”
Section: Traditional Usagesmentioning
confidence: 99%
“…8,9 Previous chemical studies of Brassica genus reported the isolation of phenolics and organic acids. [10][11][12][13] As a part of our continuing studies on medicinal plants of Bangladesh, [14][15][16][17][18] our aim was to screen B. rapa subspecies chinensis for primary analgesic and antidepressant activities. This is the first time report regarding these bioassays of this plant and it might be useful for inspiring bioactivity guided isolation of compounds from this herb.…”
Section: Brassica Rapa Subsp Chinensis (Bengali Namementioning
confidence: 99%
“…En el caso de Xanthium strumarium, que posee una proporción similar de glucósidos diterpénicos, algunos artículos proponen que el agente tóxico está presente solamente en las semillas y brotes durante el estadio de cotiledones, y su ausencia en las plantas con cuatro o más hojas (18) . Sin embargo, otros estudios aseguran que el extracto de la planta madura también posee una toxicidad importante, produciendo las mismas alteraciones observadas en la toxicidad por ATR y CATR (19) . Estos últimos coinciden con los resultados obtenidos con el extracto de hojas de la planta madura de Xanthium spinosum.…”
Section: Extrapolación De Datosunclassified